Preferential Trade Arrangements, Induced Investment, and National Income in a Heckscher-Ohlin-Ramsey Model - Joseph Francois; M. Rombout (Tinbergen Institute, 2000)
We develop a Heckscher-Ohlin-Ramsey model, combining dual techniqueswith classic geometric techniques fromtrade theory. This framework is used to explore the long-run generalequilibrium effects of regional integration(preferential trade agreements). Emphasis is placed on positivemechanics related to adjustment in the capitalstock, long-run changes in the pattern in trade, and the implicationsfor changes in long-run (steady-state)national income. The importance of relative country size and thedynamic implications for third countries are alsoaddressed.
Keywords: F15; F41; F1; 330; regionalism; trade and investment; preferential trade arrangements; Heckscher Ohlin Ramsey model; trade and growth; Außenwirtschaftstheorie; Theorie